Association between self-care and complications among patients with type 2 diabetes mellitus: A cross-sectional study - Alaa Hamza Hermis; Fakhria Jaber Muhaibes (Medical Journal of Babylon, 2023)
Background: Self-care is essential for diabetes patients to keep control of the disease and avoid complications. Self-care can help minimize these complications. Objectives: The study endeavored to examine type 2-diabtic patients’ knowledge regarding self-care management and to determine the association between self-care management and the disease complications. Materials and Methods: This study was a quantitative research of cross-sectional design on a sample of 151 patients who visited the endocrine and diabetes center in Al-Dewaynia Teaching Hospital, Iraq. Data were collected by demographic questionnaire and the Diabetes Self-Care Scale (DSCS). Results: The results showed that there was a significant association between the diabetes self-care management and both diabetic foot and neuropathy (0.002 and 0.005), respectively, whereas it was no association between the diabetes self-care management with retinopathy, cardiovascular problems, nephropathy, and hepatic problems at any significant level. Conclusion: The study revealed that individuals’ adherence to self-care management of type 2 diabetes is very poor. Enhancing patients’ and community’s regarding changing the lifestyle is essential.